Tri Hita Karana-based interactive e-worksheet for Indonesian language subjects to improve literacy skills and prevent bullying in elementary schools - Sudiana, I Nyoman; Darmayanti, Ida Ayu Made; Dewantara, I Putu Mas; Sukmayasa, I Made Hendra (Edelweiss Applied Science and Technology, 2024)
Low literacy skills and the still high number of bullying cases are two problems currently faced in schools in Indonesia. Therefore, this study aims to develop an Interactive E-Worksheet Based on Tri Hita Karana for Indonesian Language Subjects to Improve Literacy and Prevent Bullying in Elementary Schools. To achieve these goals, this study was conducted by following the development research model with the ADDIE approach consisting of five stages: analysis, design, development, implementation, and evaluation. Data in this study were collected through observation, questionnaires and tests. Data were analyzed qualitatively and quantitatively. The results of this study indicate that the developed e-worksheet is proven valid and has a good level of practicality. In addition, based on the results of the analysis using MANOVA, it was found that learning using the Interactive E-Worksheet Based on Tri Hita Karana for Indonesian Language Subjects can effectively improve students' literacy skills and understanding of bullying so that bullying prevention can be carried out optimally. Thus, the practical implication of this study is that the Tri Hita Karana-based Interactive E-Worksheet for Indonesian Language Subjects, developed to improve literacy skills and prevent bullying, can be used as teaching materials to achieve similar goals in other schools.